SASTRA MELAYU KLASIK DALAM PENGAJARAN SASTRA INDONESIA DI SMA - Sayekti, Sayekti (Widya Warta, 2009)
The genre of Classical Malay literature exists in the subject of Indonesian Language and Literature for Senior High School as part of the teaching materials for Indonesian literature. Hence, the genre intended should be taught for students. The instructional goal of Classical Malay literature is generally the same as that of Modern  Indonesian  literature,  i.e.  to  equip  students  with  capabilities  on  literary  work appreciation. The difference between Classical Malay literature and Modern Indonesian one lies on the language used as well as the narrative content. The former usually makes use of old Malay language and its narrative content is dominated by the tradition and idea of ancient society. The ability to appreciate literary works may help to enhance one’s feeling, reasoning, imaginative power, and sensitivity towards society, culture, and environment. The language used and the temporal setting, which are archaic, often become a barrier for comprehending the classical literature. In order to overcome the obstacle, teachers need to provide their class with classical literary works written in the language of close level of students’ language comprehension. In addition, the narrative content should be of appropriate level with students’ psychological development. Teachers themselves ought to be interested in the genre of Classical Malay literature and apply suitable teaching strategies, so that they are able to guide their students to benefit from the classical literary works being appreciated.